The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3389/fmicb.2021.654178
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Viable Brochothrix thermosphacta in Cold-Smoked Salmon Using PMA/PMAxx-qPCR

Abstract: The aim of this study was to develop a rapid and accurate PMA-qPCR method to quantify viable Brochothrix thermosphacta in cold-smoked salmon. B. thermosphacta is one of the main food spoilage bacteria. Among seafood products, cold-smoked salmon is particularly impacted by B. thermosphacta spoilage. Specific and sensitive tools that detect and quantify this bacterium in food products are very useful. The culture method commonly used to quantify B. thermosphacta is time-consuming and can underestimate cells in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Recently, some studies on a new DNA-intercalating agent, PMAxx, produced on the basis of PMA, would have shown greater activity and better ability to distinguish between live and dead bacteria [ 98 ]. However, PMAxx-applied research on seafood is rarely reported at present [ 62 , 67 , 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some studies on a new DNA-intercalating agent, PMAxx, produced on the basis of PMA, would have shown greater activity and better ability to distinguish between live and dead bacteria [ 98 ]. However, PMAxx-applied research on seafood is rarely reported at present [ 62 , 67 , 99 ].…”
Section: Discussionmentioning
confidence: 99%